Sex and Immunogen-Specific Benefits of Immunotherapy Targeting Islet Amyloid Polypeptide in Transgenic and Wild-Type Mice - Krishnamurthy, Pavan K.; Rajamohamedsait, Hameetha B.; Gonzalez, Veronica; Rajamohamedsait, Wajitha J.; Ahmed, Nawal; Krishnaswamy, Senthilkumar; Sigurdsson, Einar M. (Frontiers in Endocrinology, 2016)
Type 2 diabetes mellitus is characterized by the deposition of islet amyloid polypeptide (IAPP) as amyloid in islets, a process thought to be toxic to β-cells. To determine the feasibility of targeting these aggregates therapeutically, we vaccinated transgenic (Tg) mice that overexpress human IAPP and were fed a high fat diet to promote their diabetic phenotype. Our findings indicate that prophylactic vaccination with IAPP and its derivative IAPP7-19-TT, protects wild-type female mice, but not males, from obesity induced early mortality, and the derivative showed a strong trend for prolonging the lifespan of Tg females but not males. Furthermore, IAPP7-19-TT immunized Tg females cleared a glucose bolus more efficiently than controls while IAPP immunized Tg females showed an impaired ability to clear a glucose bolus compared to their adjuvant injected Tg controls. Interestingly, IAPP or IAPP7-19-TT treatments had no effect on glucose clearance in transgenic males. Overall, these beneficial effects of IAPP targeted immunization depend on transgenic status, sex and immunogen. Hence, future studies in this field should carefully consider these variables that clearly affect the therapeutic outcome. In conclusion, IAPP targeting immunotherapy may have benefits in patients with type 2 diabetes.